Effect of patient sorting done by nurses on care request management in primary care emergency services - Pérez Romero, Genoveva; Jiménez García, Ángela; Hueso Montoro, Cesar; Montoya Juárez, Rafael; García Caro, María Paz (Investigación y Educación en Enfermería, 2024)
Objective. To determine the influence of patient sorting done by nurses in primary care emergency services on care priorities and discharge referrals, both in general and in relation to the reasons for consultation. Methods. Descriptive retrospective study. Variables were compared before and after the involvement of nurses in sorting patients in the primary care emergency services of the Granada Health District (Andalusia, Spain). 41,295 records were analyzed, 18,663 before and 22,632 two years after the inclusion of nurses. The reasons for consultation, priority levels, and types of discharge referral during the two study moments were compared. Results. Regarding the reasons for consultation, it was observed that the percentages of malaise (p<0.001) and diseases of the genitourinary system (p<0.001) increased, while fever (p<0.001), among others, decreased. In the two-year measurement period after sorting done by nurses was implemented, type IV priorities increased in percentage (p<0.001) and type V priorities decreased (p<0.001). Discharges to home decreased (p<0.001), while family physician referrals increased (p<0.001). Conclusion. The participation of nurses in the sorting of patients in primary care emergency services was related to significant changes in priority assignment, discharge referrals, and management of the reasons for consultation, showing an improvement in patient care autonomy and in the resolution of minor clinical problems in the emergency room.